Surveillance for hepatocellular carcinoma in people of African ancestry with HIV and Hepatitis B. (February 2022) - Patel, Nisha; Post, Frank A
Current guidelines recommend six-monthly ultrasound surveillance for hepatocellular carcinoma (HCC) in high risk, non-cirrhotic people with HIV and hepatitis B co-infection (HBV). African or Asian ethnicity is considered a risk factor for the development of HCC. Risk stratification scores for HCC have been generated in HBV mono-infected Caucasian and Asian populations, however they not been validated in people with HIV or those of African ancestry. We undertook an audit of HCC surveillance in HIV/HBV co-infected individuals of African ancestry who participated in the GEN-AFRICA study. Electronic patient records were reviewed for liver disease characteristics. REACH-B and PAGE-B scores were calculated to ascertain whether individuals at greatest risk of developing HCC were being targeted for ultrasound surveillance. 76 individuals (median age 51 years, 96% HIV RNA < 200 copies/mL, 87% HBV DNA <20 IU/mL) were included. 7% of participants had undergone six-monthly HCC surveillance by liver ultrasound (5% of those at low risk; 9% at intermediate or high risk). Adherence to HCC surveillance was poor and not targeted to those at highest risk. Lack of an evidence base for intensive HCC screening of non-cirrhotic, HIV/HBV co-infected individuals of African ancestry may have contributed to the poor uptake of biannual HCC ultrasound surveillance.